MENDIDIK UNTUK KEHIDUPAN BERDASARKAN KOMPETENSI GURU KRISTEN DI INDONESIA (EDUCATION FOR LIFE BASED ON CHRISTIAN TEACHER COMPETENCE IN INDONESIA) - Edym Bahapol; Youke Singal (QUAERENS: Journal of Theology and Christianity Studies, 2020)
High quality education is very important for the progress of a society or nation. John Fitgerald Kennedy, former President of the USA 1961-1963, said "The development of a nation can not be swifter than the development in education. That is, if we want to advance our society and nation, then we must advance and improve the quality of our education. On the other hand, experts believe that science is power and education is a future investment (knowledge is power and education is investment in the future). So not the act of educating is very important and essential so the purpose of writing is how the act of educating in Christianity is aimed at the life of God's people themselves as a whole. Pendidikan yang berkualitas tinggi sangat penting artinya bagi kemajuan suatu masyarakat atau bangsa. John Fitgerald Kennedy, mantan Presiden USA 1961-1963, mengatakan “The development of a nation can not be swifter than the development in education. Artinya, kalau kita ingin memajukan masyarakat dan bangsa kita, maka kita harus lebih dahulu memajukan dan meningkatkan kualitas pendidikan kita. Di pihak lain, para pakar berpendapat bahwa ilmu pengetahuan adalah kekuatan dan pendidikan adalah investasi masa depan (knowledge is power and education is investment in the future). Maka tidaklah tindakan mendidik merupakan hal yang sangat penting dan esensial sehingga tujuan penulisan adalah bagaimana tindakan mendidik dalam kekristenan adalah bertujuan untuk kehidupan umat Tuhan itu sendiri secara utuh.